Relationship of Knowledge and Perceptions Towards Triage Skills on Nurses in The Emergency Department (Indonesian Contemporary Nursing Journal (ICON Journal), 2022)
Introduction: The large number of patients visiting the emergency department requires triage system. The implementation of triage really requires the skills possessed by nurses who have good knowledge and positive perceptions about triage. The purpose of this study was to determine the relationship between knowledge and perceptions of nurses with triage skills on nurses in the Emergency Department of RSUP Dr. M. Djamil, Padang. Method: This study is a quantitative study with an analytical descriptive type using cross-sectional approach. The sampling technique used convenience sampling technique with the criteria of emergency department nurses who work in the triage area with respondent participated as 34 nurses. Data collection using instruments, as knowledge questionnaire, perception questionnaire, and TSQ (Triage Skills Questionnaire). Result: There is a relationship between knowledge and triage skills in nurses with p value 0,015 and no relationship between nurses’ perceptions and triage skills with p value 0,063. Conclusion: Good knowledge for nurses can help nurses in carrying out triage actions properly so that they motivate nurses to categorize patients correctly based on the level of emergency. Training, seminar or long-life learning on triage will be able to assist nurses in improving nurses triage skills in the emergency department.
Keywords: Knowledge; Perception; Skill; Triage